2009
DOI: 10.1186/1471-2474-10-108
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between spasticity in young children (18 months of age) with cerebral palsy and their gross motor function development

Abstract: Background: It is thought that spasticity has an influence on the development of functional motor abilities among children with cerebral palsy (CP). The extent to which spasticity is associated with the change in motor abilities in young children with CP has not been established. The objective of this study is to evaluate the relationship of initial spasticity in young children with CP and their gross motor function development over one year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 29 publications
3
29
0
4
Order By: Relevance
“…Gorter et al [29], who assessed the relationship between spasticity and gross motor function of children with 18 months old, showed that the non-affected children presented no difficulties, however, the relationship between spasticity and gross motor function decreased when including other characteristics such as muscle weakness, sensi-tivity disturbances, perception, cognition and the child's environment, which the ultimate may have influence on gross motor function.…”
Section: Discussionmentioning
confidence: 99%
“…Gorter et al [29], who assessed the relationship between spasticity and gross motor function of children with 18 months old, showed that the non-affected children presented no difficulties, however, the relationship between spasticity and gross motor function decreased when including other characteristics such as muscle weakness, sensi-tivity disturbances, perception, cognition and the child's environment, which the ultimate may have influence on gross motor function.…”
Section: Discussionmentioning
confidence: 99%
“…We recruited a sample of convenience from a spasticity management service in a tertiary setting that had a higher proportion of children presenting with GMFCS levels I to III. Based on weak association of spasticity with gross motor function, [26][27][28] we believe it unlikely that GMFCS level would affect the ability of the ASAS to detect and score spasticity.A second limitation is the distribution of our ASAS scores, with many zero scores and few scores of four. This is consistent with our clinical expectation of lower spasticity scores in children who have been engaged in tertiarylevel spasticity management.…”
mentioning
confidence: 93%
“…Spasticity was redefined as 'disordered sensori-motor control, resulting from UMN lesion, presenting as intermittent or sustained involuntary activation of muscles' (Pandyan et al, 2005). In the clinical setting, spasticity is assessed as a velocity-dependent increased resistance to passive muscle stretch (Gorter, Verschuren, van Riel, & Ketelaar, 2009).…”
Section: Introductionmentioning
confidence: 99%